Wage dynamics and worker mobility during deep recessions - Anete Pajuste; Hernán Ruffo (Baltic Journal of Economics, 2019)
We provide empirical evidence of the relationship between downward wage rigidity and unemployment volatility by comparing wage dynamics and worker mobility during the Great Recession in two countries where wages adjusted very differently: Latvia and Spain. Using a panel of social security administrative data, we find that wages in Spain were rigid even during periods of rising unemployment. In contrast, Latvian wages were reduced and wage cuts affected 60 percent of jobs. At the same time, the elasticity of workers' transition rates into and out of unemployment to productivity shocks was four times higher in Spain than in Latvia, and these responses were more persistent in Spain. This evidence is consistent with theoretical models that show that unemployment volatility is higher when wages are rigid.
Keywords: 330